Concrete Horizons: Romantic Irony in the Poetry of David Malouf and Samuel Wagan Watson - Barratt-Peacock, Ruth (MUSE: Munich Studies in English, 2020)
Drawing on Bernd Mahr's model theory, this volume introduces a new approach to Romanticism in contemporary Australian literature. Focusing on two very different authors, David Malouf and the Indigenous poet Samuel Wagan Watson, this book highlights their similarities rather than their differences. It is the first book-length study dedicated specifically to each author's poetic oeuvre. Comprehensive readings reveal that an ironic dialectic underpins how each poet writes from within a disjunct of culture and environment following colonisation, finding hope in dialogue and a productive process of negative assertion. The theoretical framing of Romanticism developed here effectively rehabilitates Romanticism as a productive paradigm in contemporary Australian poetry.